2015
DOI: 10.1007/s10750-015-2186-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aluminum treatment efficiency on water quality and internal phosphorus cycling in six Danish lakes

Abstract: If dosed sufficiently relative to the pool of excess phosphorus (P) in the lake sediment and lake water, aluminum (Al) is hypothesized to block sediment P release and thereby improve water clarity in eutrophic lakes. Aluminum has been used in [200 lakes worldwide, but in some 30% of the known cases water clarity did not improve beyond the first year, likely because of underdosing or continued high external P loading. We evaluate the viability of the aluminum dosing hypothesis for six Danish lakes that received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Empirically, it has been suggested that Al doses must be at least 10 times the targeted P mass (Jensen et al 2015, Huser et al 2016b. A minimum ratio of Al:P mass of 10:1 is supported by treatment results from Cape Cod, Massachusetts , whereas higher Al:P ratios may be necessary to overcome interferences and inefficiencies in some lakes (Huser 2017, James 2017.…”
Section: Dose Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, it has been suggested that Al doses must be at least 10 times the targeted P mass (Jensen et al 2015, Huser et al 2016b. A minimum ratio of Al:P mass of 10:1 is supported by treatment results from Cape Cod, Massachusetts , whereas higher Al:P ratios may be necessary to overcome interferences and inefficiencies in some lakes (Huser 2017, James 2017.…”
Section: Dose Determinationmentioning
confidence: 99%
“…Certainly continued inputs from watersheds are important, and gradual burial of the treated sediment will lead to renewed internal loading, but that process seems to be slow in stratified lakes and where the watershed:lake area ratio is low (Huser et al 2016b). Two internal mechanisms that control internal P loading after treatment are upward migration of P from below the inactivated zone in the sediment (Lewandowski et al 2003, James 2017) and release from organic matter through decay (Jensen et al 2015). Both can be important P sources and are likely to contribute in most lakes.…”
Section: Duration Of Benefitsmentioning
confidence: 99%
“…Important issues are the choice of appropriate P adsorptive, dose, and the longevity of an application (Zamparas and Zacharias 2014). Longevity might be impaired by low doses (Cooke et al 2005;Jensen et al 2015), chemical aging (Søndergaard et al 2007;de Vicente et al 2008), or physical redistribution in lake sediment. A single big dose might be less effective than smaller doses due to aging of the active compound (de Vicente et al 2008;Jensen et al 2015).…”
Section: Nutrientsmentioning
confidence: 99%
“…Longevity might be impaired by low doses (Cooke et al 2005;Jensen et al 2015), chemical aging (Søndergaard et al 2007;de Vicente et al 2008), or physical redistribution in lake sediment. A single big dose might be less effective than smaller doses due to aging of the active compound (de Vicente et al 2008;Jensen et al 2015). Douglas et al (2016) reviewed solid-phase phosphorus adsorbents, categorized in: naturally occurring minerals, soils, suspended particles or earth materials; natural or synthetically produced materials; modified clay mineral or soils; and mining, mineral processing, and industrial by-products.…”
Section: Nutrientsmentioning
confidence: 99%
“…Aluminum (Al)-salts have been used to reduce P cycling in lakes around the world for nearly half a century (Landner, 1970;Kennedy et al, 1987;Cooke et al, 2005;Jensen et al, 2015). The success of past treatments has varied greatly, with studies showing longevity of water quality improvements ranging from months to 20 years (Welch and Cooke, 1999).…”
Section: Introductionmentioning
confidence: 99%